Fiscal severity and the choice of budget gap closing strategies. Issue 4 (7th June 2018) - Guo, Hai (David); Neshkova, Milena
Abstract : The great recession of 2008 forced US local governments to pursue a series of measures to maintain a balanced budget. The authors investigated local governments' response to the great recession with a focus on Florida, where a crash in the housing market led to a severe erosion of the property tax base. Following the classic cutback management theory, the authors examine how the severity of fiscal stress affected the choice of budget-balancing strategies by Florida's local governments. The severity of fiscal stress was found to affect not only the number of budget gap closing strategies but also the pattern of adoption of these strategies consistent with the administrative response model.